Efetividade clínica do Análogo glargina no Diabetes Tipo 1: revisão sistemática e Coorte histórica - Lays Pires Marra (2016)
BACKGROUND: Diabetes mellitus (DM) has taken epidemic proportions in recent years, setting up a growing problem of global public health, mainly by causing damage to the patient in the clinical aspects, social, economic and quality of life, given its potential morbidity andmortality. The treatment of type 1 diabetes mellitus (T1DM) patients consists basically of the replacement of insulin not produced endogenously. The use of insulin analogs for the treatment of T1DM has been widespread, but the actual therapeutic benefits still requireevidence. OBJECTIVE: To evaluate the clinical effectiveness of analog glargine in the treatment of patients with T1DM compared to NPH insulin.METHODS: A) Systematic Review -It was performed a systematic review (SR) with metaanalysis. SR were included cohort studies and registration available in PUBMED, LILACS, CENTRAL (accessed until June 2015), including manual and gray literature search. The meta-analysis was conducted in Review Manager® 5.2 software. The primary outcomesassessed were: glycohemoglobin (HbA1c), weight gain and the occurrence of hypoglycemia. The assessment of methodological quality was performed using a Newcastle scale. B) Historical Cohort It was performed a historical cohort study with T1DM patients, whoreceived glargine analog through specialized component / high cost of State Health Secretariat of Minas Gerais. It was built a database of these individuals, registered as protocol using glargine analog in the state of Minas Gerais. The cohort consisted of patients using glargineanalog 6 months ago and whose inclusion in the program occurred between January / 2011 and January / 2015. These patients were compared to themselves before - when in use of NPHinsulin - and after using the analog glargine. We evaluated the HbA1c and glycemic control of patients. RESULTS: A) Systematic Review -From a total of 796 publications, 11 studies were included. The meta-analysis favored glargine analog in HbA1c outcomes (adult patients) andhypoglycaemia (p <0.05), but without reaching glycemic control (HbA1c around 7%). The methodological quality of the studies was moderate and 45% of them were funded by pharmaceutical industry. B) Historical Cohort There were included 580 patients. The analysis demonstrated a statistically significant reduction in HbA1c values of 8.80 ± 1.98% inuse of NPH to 8.54 ± 1.88% (p = 0.001) after 6 months of using the analog glargine. The frequency of patients with glycemic control varied from 22.6% in use of NPH to 26.2% in use of glargine analog. The average daily dose of basal insulin ranged from 35.23 ± 15 IU NPH8 when in use to 34.38 ± 15 IU after six months of use of analog glargine (p = 0.018). The post hoc analysis using the Tukey test showed statistically significant difference in the mean dose of glargine similar among patients 06 and 12, which are smaller compared the doses used by other age groups. Patients with and without glycemic control does not show any statistically significant differences in all variables. CONCLUSIONS: A) Systematic Review Taking into account the high heterogeneity of the studies, the discrete value presented by the estimated effect on the effectiveness and safety outcomes, potential conflicts of interest of the included studies and the cost of treatment in theface of existing therapeutic alternatives, there is no support for the recommendation on differential therapy with available analogs. The role of similar treatment in DM1 should be better determined by effectiveness studies of good methodological quality, in order to assess the long-term safety profile, as well as economic evaluation of therapeutic alternatives. B) Historical Cohort The evaluation of the patient groups that have glycemic control after six months of use of glargine analog concluded that there is no association between use of glargine analog and characteristics of the patient or treatment. Since the differences betweenthem are minimal, we can assure that the NPH insulin is as effective as glargine analog, there is no justification for excessive or unreasonable difference of cost between them. It becomes imposing and imminent to reevaluate sourcing strategy of the drug in the Brazilian states and taking renegotiation measures on prices.